Financial Management's Response to Tightening Regulation in the Aftermath of Global Financial Scandals - Marota, Rochman (Advances in Management & Financial Reporting, 2025)
Purpose: This study examines financial management's strategic responses to tightening regulatory frameworks after global financial scandals. It focuses on how organizations maintain compliance while balancing operational efficiency, highlighting the role of governance strategies, organizational culture, and technology in financial reporting processes. Research Design and Methodology: A systematic literature review (SLR) approach synthesized findings from peer-reviewed journal articles and relevant academic publications. The study integrates insights from recent research to explore the interplay between regulatory adherence, governance frameworks, and organizational performance, focusing on sector-specific dynamics and technological innovations. Findings and Discussion: The study identifies that companies effectively navigating stringent regulations often implement advanced technologies such as blockchain and data analytics to enhance reporting accuracy and mitigate risks of manual errors. A strong organizational culture emphasizing transparency and accountability was found to improve compliance and foster stakeholder trust. However, companies with limited resources face challenges in adopting such technologies, which may affect their ability to meet regulatory requirements efficiently. Sectoral differences also play a significant role, with the financial sector adapting more readily to regulatory changes than other industries. Ethical leadership and cross-functional collaboration were critical in addressing cultural resistance and ensuring robust regulatory implementation. Implications: The study provides practical recommendations for financial managers to enhance compliance through capacity-building initiatives, investment in automated reporting systems, and strengthening internal control mechanisms. For policymakers, it suggests the importance of tailoring regulations to industry-specific needs to avoid overburdening organizations and ensure more effective governance practices.